DMAb inoculation of synthetic cross reactive antibodies protects against lethal influenza A and B infections - Sarah T. C. Elliott (Nature Portfolio, 2017)
Nucleic acid delivery: Instant, wide-ranging protection against influenza A and B A novel innoculation technique involving the injection of antibody-producing plasmid DNA has shown to be effective against influenza in mice. The flu is responsible for up to half a million deaths each year and up to five million cases of severe disease, while also posing a substantial pandemic threat, even with our current repertoire of vaccines. A team of researchers led by Sarah Elliott and David Weiner of The Wistar Institute of Anatomy and Biology, Philadelphia, developed potent plasmid-based constructs that, once injected, entered hosts’ cells and utilized cellular machinery to encode antibodies protective against a range of influenza A and B subtypes. DNA inoculation conferred acute protection from disease, with treated individuals also being immune to subsequent exposure. This approach warrants further investigation as an alternative technology for practical delivery of monoclonal antibody therapeutics.